2023
DOI: 10.1039/d2fo03105a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening of novel tyrosinase inhibitory peptides from a pearl shell meat hydrolysate by molecular docking and the anti-melanin mechanism

Abstract: Pearls is an edible and medicinal resource with whitening activity and nutritional effects in China. In the previous study, we found that the pearl shell meat hydrolysate had dual activities...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…The binding energy for molecular docking reflects the tightness of the binding of the ligand to the receptor, and a lower binding energy score indicates that the ligand binds the receptor more tightly. 60,61 The results showed that P5 (−5.6 kcal mol −1 ) obtained the lowest binding energy, which was consistent with the results of cell proliferation. We speculated that phosphate groups played a key role in the process of P5 binding with EGFR, leading to a tighter binding of the P5-EGFR complex.…”
Section: In Silico Molecular Docking Of Peptides and Egfrsupporting
confidence: 86%
See 1 more Smart Citation
“…The binding energy for molecular docking reflects the tightness of the binding of the ligand to the receptor, and a lower binding energy score indicates that the ligand binds the receptor more tightly. 60,61 The results showed that P5 (−5.6 kcal mol −1 ) obtained the lowest binding energy, which was consistent with the results of cell proliferation. We speculated that phosphate groups played a key role in the process of P5 binding with EGFR, leading to a tighter binding of the P5-EGFR complex.…”
Section: In Silico Molecular Docking Of Peptides and Egfrsupporting
confidence: 86%
“…It was found that the shorter the distance of the hydrogen bond formed between the receptor and the ligand, the more stable their binding. 60 In this study, pSER15, pSER17, pSER18, and pSER19 of P5 formed 6 hydrogen bonds with EGFR, and their hydrogen bond distances were 2.0 Å (pSER15-GLN408), 2.2 Å (pSER17-ARG29), 2.8 Å(pSER17-ARG29), 2.8 Å(pSER17-ARG29), 2.6 Å (pSER18-ARG29), 1.9 Å (pSER19-HIS409), and 2.7 Å (pSER19-GLN411), which had a mean hydrogen bond distance of 2.37 Å. SER17, SER18, and SER19 of P5-0 formed 2 hydrogen bonds with EGFR and their hydrogen bond distances were 2.6 Å (SER18-SER11) and 2.2 Å (SER19-ASN40), while their mean hydrogen bond distance was 2.4 Å. The results showed that pSER15, pSER17, pSER18, and pSER19 of P5 produced shorter mean hydrogen bond distances than SER18 and SER19 of P5-0, suggesting that the phosphorylation structure in P5 played an essential role in binding EGFR.…”
Section: Resultsmentioning
confidence: 99%